2018
DOI: 10.4236/ojo.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

Another Look at Skeletal Maturation Using Hand Wrist and Cervical Vertebrae Evaluation

Abstract: Introduction and Aims-The Growth stage of a patient can have considerable influence on diagnosis, treatment goals, timing and planning and the eventual outcome of orthodontic/orthopedic treatment. The purpose of this study was to analyze associations between the cervical vertebrae maturation score (CVMS) and skeletal maturation index (SMI). The second objective was to determine the reproducibility of the measurements on lateral cephalograms and hand-wrist radiographs. Materials and Methods-Lateral cephalometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Pemahaman mengenai pertumbuhan dan perkembangan kraniofasial pasien sangat penting dalam membantu menegakkan diagnosis, merencanakan perawatan, dan keberhasilan perawatan. 1,2 Waktu perawatan ortodonti berhubungan dengan keparahan dan tipe maloklusi yang dikaitkan dengan tingkat maturitas pasien. Rata-rata perawatan ortodonti dilakukan pada masa tumbuh kembang.…”
Section: Pendahuluanunclassified
“…Pemahaman mengenai pertumbuhan dan perkembangan kraniofasial pasien sangat penting dalam membantu menegakkan diagnosis, merencanakan perawatan, dan keberhasilan perawatan. 1,2 Waktu perawatan ortodonti berhubungan dengan keparahan dan tipe maloklusi yang dikaitkan dengan tingkat maturitas pasien. Rata-rata perawatan ortodonti dilakukan pada masa tumbuh kembang.…”
Section: Pendahuluanunclassified
“…Beginning in the 1970s, several attempts at cervical vertebrae analysis were performed, with the most popular one being modified by Bacetti et al (4) . Mandibular growth alterations in growing subjects and the stages of cervical vertebrae maturation (CVM) have both been shown to be reliable indicators of mandibular skeletal maturity (5) . According to Salagnac et al (6) , the mandible, upper face, and cervical spine all grew vertically at associated anatomical and physiological rates.…”
Section: Introductionmentioning
confidence: 99%
“…The craniofacial bone relevant to the treatment of crowding is the mandible, as measured by the mandibular length. [7][8][9][10] Recent studies showed that cervical vertebral growth is closely related to mandibular maturation and growth. In particular, mandibular growth peaks have been reported to occur concurrently in CVM stages 3 and 4.…”
Section: Introductionmentioning
confidence: 99%